A Study On Puerperal Events And Postpartum Reproductive Performance In Kankrej Cows - Naikoo, Mehrajuddin; Dhami, A.J.; Ramakrishnan, Ammu; Parmar , B.C.; Divekar, B.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A study was carried out on 42 normal parturient Kankrej cows of 2nd to 4th parity on an organized farm during the period from 2010-12 to evaluate the puerperal events and postpartum fertility with and without use of oestrus induction / synchronization protocols (viz., Ovsynch, CIDR, Ovsynch+CIDR, Cosynch and PGF2α) around day 90-95 postpartum in anoestrus/suboestrus cows. Palpation per rectum was carried out at five days interval from day 10 to 40 postpartum, to monitor ovarian changes and uterine involution, and around day 70-90 at 10 days intervals to confirm anoestrus/ suboestrus condition. The plasma progesterone levels were estimated by RIA at 10 days interval from calving till 140 days postpartum. The birth weight of calf, time required for expulsion of fetal membranes and weight of expelled fetal membranes were 24.29 ± 1.54 kg, 5.04 ± 2.01 hrs and 2.84 ± 0.76 kg, respectively. Complete uterine involution was noted in Kankrej cows by mean interval of 36.80 ± 1.21 (range 32-45) days postpartum. The interval for occurrence of first oestrus postpartum clinically and through plasma progesterone profile was 105.49 ± 1.66 (range 86-106) and 56.42 ± 3.88 (range 30-80) days, respectively (P
Keywords: Kankrej cows; Puerperal events; Plasma progesterone; Oestrus synchronization; Fertility